Math virtual assistant

About Snapxam Calculators Topics Go Premium
ENGESP
Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Solve the equation 1-1(2u-3)/4=(2-5u)/3-3u

1-\frac{2u-3}{4}=\frac{2-5u}{3}-3u

Step by step solution

Problem

$1-\frac{2u-3}{4}=\frac{2-5u}{3}-3u$

Show full step-by-step solution

Answer

$-\left(\frac{2-5u}{3}-3u\right)-\frac{2u-3}{4}+1=0$
$1-\frac{2u-3}{4}=\frac{2-5u}{3}-3u$

Main topic:

Equations

Used formulas:

0

Time to solve it:

0.3 seconds